PENGARUH KOMUNIKASI BAGI KESEHATAN MENTAL ANAK - Anggelica Anggelica; Chontina Siahaan (Prodi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, UKI, Jakarta, 2021)
The formation of children's character is very important to note from an early age. In the formation of a child's character, the main role that shapes the identity of the child is the family. One way to shape the character of the child is through communication. Family communication is communication that occurs within the family, by interacting with one another and involving all family members as well as a forum for taking and developing values ​​that can be used as a guide in character building. Communication in the family has several types, for example, communication does not only include two people who are conversing, but communication also includes behavior. The pattern of communication formed in a family will have an impact on family members, especially on the mental health of the family. Family communication is both positive and negative. If family communication is positive and educational, then the impact that will be given to the child will be positive. Vice versa, if family communication is negative or toxic, then the impact that will be given to the child will be negative, even disturbing the child's mental health. Poor mental health, especially from an early age, can lead to more serious behavioral disorders due to lack of mental and emotional stability, and can also interfere with the child's social life. For this reason, in family communication, each family member must pay attention to each other when communicating, so that what is communicated becomes a positive use and begins to pay attention to mental health among family members from an early age.